DESIGN OF AN INTERPRETER SQL - Hinojosa L., Hilmar (2002)
The present articie presents in brief forirrí the most excellent topics in the design of an Interpreter of SQL, which consists on a program that it allows an user to create and to manipulate an own database, making use of sentences standard SQL.